6x-15=9+3x

Simple and best practice solution for 6x-15=9+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-15=9+3x equation:


Simplifying
6x + -15 = 9 + 3x

Reorder the terms:
-15 + 6x = 9 + 3x

Solving
-15 + 6x = 9 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-15 + 6x + -3x = 9 + 3x + -3x

Combine like terms: 6x + -3x = 3x
-15 + 3x = 9 + 3x + -3x

Combine like terms: 3x + -3x = 0
-15 + 3x = 9 + 0
-15 + 3x = 9

Add '15' to each side of the equation.
-15 + 15 + 3x = 9 + 15

Combine like terms: -15 + 15 = 0
0 + 3x = 9 + 15
3x = 9 + 15

Combine like terms: 9 + 15 = 24
3x = 24

Divide each side by '3'.
x = 8

Simplifying
x = 8

See similar equations:

| 13x+17y=19 | | 2x+10=6+4x | | -7(x+4)+4x+7=8x+6 | | 7/60=a | | 2x-16=-128 | | 1.4(x)=2x-3 | | 2/5*7/-6*-7=a | | .5(x)=2x-3 | | x+18=106 | | 2/5*7/-6*-7 | | -1(x)=2x-3 | | 1(x)=2x-3 | | 4/-6+2=-1 | | 3(x)=2x-3 | | 3(6x-4)-4(x+7)=6x-96+x | | 4(4x+1)=3x-4(6-x)8 | | 2.75(x)=2x-3 | | -7(x-2)=-4 | | 0.86=exp(-6.2831*f) | | 0.86=exp(-2*pi*f) | | (3x-2)2=(2x+3)2 | | 9^4x*27^2-3x=1/9 | | x^5x^7/x^6 | | 5-2q=3Q | | 6(4+2x)-(8x-22)=68 | | X^2+0.2x-0.48=0 | | 3(-6)+2y=6 | | -6(x-2)+4(5n-3)=-36 | | 4(b+1)=-2(b+2) | | 8+x-1/x+4 | | -5-2(-6)=7 | | 49w^2-16w=0 |

Equations solver categories